2018
DOI: 10.2174/1381612824666171204151209
|View full text |Cite
|
Sign up to set email alerts
|

The Overlap Between Binge Eating Behaviors and Polycystic Ovarian Syndrome: An Etiological Integrative Model

Abstract: Studies indicate that Polycystic Ovarian Syndrome (PCOS) features (e.g. insulin instability, food cravings, overproduction of androgens and menstrual irregularities) are associated with increased appetite, impaired impulse control and feelings of body dissatisfaction. Counter intuitively, binge eating behaviors have been shown to reinforce PCOS symptomatology, precipitating concurrently body dissatisfaction, weight gain, insulin instability and overproduction of androgens. The present systematic literature rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 78 publications
1
28
0
1
Order By: Relevance
“…To conclude, the current review has shown that women with PCOS have elevated prevalence and risk factors for binge eating behavior, such as overweight and/or obesity,negative body image, depression and anxiety37,80 The suggested links between PCOS and binge eating are not yet well understood,67 but it is likely that they may include metabolic (hyperandrogenism), hormonal (insulin resistance), and psychological (body dissatisfaction, depression, anxiety) factors. The interaction of these factors likely is complex in nature.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…To conclude, the current review has shown that women with PCOS have elevated prevalence and risk factors for binge eating behavior, such as overweight and/or obesity,negative body image, depression and anxiety37,80 The suggested links between PCOS and binge eating are not yet well understood,67 but it is likely that they may include metabolic (hyperandrogenism), hormonal (insulin resistance), and psychological (body dissatisfaction, depression, anxiety) factors. The interaction of these factors likely is complex in nature.…”
Section: Discussionmentioning
confidence: 95%
“…Hyperandrogenism is implicated in PCOS9 and binge eating behavior63,64 and has frequently been linked to the causation of menstrual irregularities, including amenorrhea, and a delay and/or lack of ovulation 65,66. These menstrual irregularities may lead to increased hunger and psychological distress, potentially resulting in an increase in binge eating frequency 61,67…”
Section: What Are the Connections Between Pcos And Binge Eating Behavmentioning
confidence: 99%
See 2 more Smart Citations
“…Immigrants have also been reported to have a reduced risk of eating disorders compared to non-immigrant populations [28]. Within a PCOS context, current literature focuses on psychological comorbidities such as low self-esteem and severe psychological distress as plausible risk factors for the development of disordered eating and eating disorders [6,12,15,29]. There are, however, currently no studies identifying demographic factors that may link PCOS to disordered eating or eating disorders, including country of birth, Indigenous (Aboriginal or Torres Strait Islander) status, BMI or age.…”
Section: Introductionmentioning
confidence: 99%